Methods in Making Steel-Copper Sandwich Laminates Materials - Arianto Leman Soemowidagdo; Tiwan Tiwan (Department of Mechanical Engineering Education, 2019)
This research is aimed at developing a method to make steel-copper sandwich laminate materials. The research focused on the method of developing the sandwich material. In a method I, the steel plate arrangement is heated up to austenite temperature and subsequently, a molten copper is poured into it. In method II, the steel plate arrangement is immersed into a molten copper in a temperature of 1200 °C. The result shows that in the method I, the diffusion on the interface layer of steel-copper sandwich laminate is unemployed because of an occurrence of oxidation on the steel surface. On the contrary, in method II the diffusion on the interface of steel-copper sandwich laminate is indicated by higher shear stress, which is 231.88 N/mm2. However, the immersing method needs to be improved to give better products, since cavities caused by trapped air still exist and are reducing the quality of the laminates.Penelitian ini ditujukan untuk mengembangkan metode pembuatan laminat baja-tembaga. Penelitian difokuskan pada metode pembuatan laminat. Pada metode I, susunan pelat baja dipanaskan hingga suhu austenit dan kemudian tembaga cair dituangkan. Metode II adalah merendam susunan pelat baja ke dalam tembaga cair bersuhu 1200 0C. Hasil penelitian menunjukkan bahwa pada metode I tidak terjadi difusi pada lapisan antarmuka laminat baja-tembaga karena permukaan baja mengalami oksidasi saat dipanaskan. Sebaliknya, metode II menunjukkan terjadi difusi pada antarmuka laminat baja-tembaga dengan tegangan geser tertinggi 231,88 N/mm2. Namun, metode II harus diperbaiki untuk memberikan produk yang lebih baik karena masih terdapat rongga akibat udara yang terjebak dan mengurangi kualitas laminat.